Audit model using controls from ISO/IEC 27002 for the information security of electronic voting based on IoT and Blockchain - Paredes, Edson (2023)
In recent years, significant progress has been made in the integration of technologies in voting systems with the aim of improving the transparency of the process. This study proposes an audit model based on the ISO/IEC 27002 standard to evaluate electronic voting systems that make use of Blockchain technology and the Internet of Things (IoT), with the aim of improving security in voting processes. To validate this model, an evaluation of the security control was carried out by applying this international standard to a voting system that integrates Blockchain and IoT. In our analysis of 6 security controls applied to the reality of electronic voting, the system passed all established tests; Therefore, it can be concluded that the risk of compromising system information has been significantly mitigated. This research contributes to the advancement of the security of electronic voting systems and provides a solid foundation for future developments in this field. The combination of emerging technologies and international standards promotes trust, security and therefore mitigates any risk of compromising an electronic voting system by following the best practices of the international standard ISO/IEC 27002.